Voltammetric Sensors for the Simultaneous Quantification of Natural Phenolics in Coffee and Citrus Juices - Anastasiya Zhupanova; Guzel Ziyatdinova (Engineering Proceedings, 2023)
Phenolic antioxidants of various groups are important nutrients in the human diet, providing positive health effects. Nevertheless, these effects are dose dependent and require the control of natural phenolic contents in their sources. Coffee and citrus juices containing significant amounts of hydroxycinnamic acids and flavanones, respectively, are among the most widely consumed beverages all over the world. The electroactivity of phenolics allows the application of voltammetric sensors for quantification purposes. Highly sensitive and selective voltammetric sensors for the simultaneous quantification of hydroxycinnamic (caffeic (CA), ferulic (FA), and p-coumaric(p-CA)) acids and flavanones (hesperidin and naringin) have been developed for the first time using glassy carbon electrodes modified with single-walled carbon nanotubes functionalized via polyaminobenzene sulfonic acid (f-SWCNTs) and polymeric coverages from triphenylmethane dyes (phenol red (PR) or aluminon). Polymeric layers have been obtained in potentiodynamic modes. The conditions of the dye’s electropolymerization have been optimized using the voltammetric response of hydroxycinnamic acids or flavanone mixtures. Three separated oxidation peaks of CA, FA, and p-CA at the electrode with polyPR as well as hesperidin and naringin at the polyaluaminon-modified electrode have been observed. The oxidation currents are significantly increased comparing those at the bare glassy carbon (GCE) and carbon nanotube-modified electrodes. Both sensors provide a highly sensitive response to target analytes in the differential pulse voltammetric mode. Other natural phenolics of various classes do not affect the response of the sensors developed to the target analyte. The quantification of hydroxycinnamic acids in coffee and flavanones in orange and grapefruit juices has been successfully realized.